Sift : the elements of great baking - Lamb, Nicola (Clarkson Potter, 2024)
"An essential guide to baking that takes away the fear of baking failure by combining easy-to-follow, science-based advice with 100 reliable and delicious recipes for both novices and more experienced bakers--from a renowned pastry chef. "Her palate and mind thrill me in equal measure and I cannot wait to read, learn from, and celebrate this book."--Samin Nosrat Sift begins with the foundational ingredients that underpin great bakes--flour, sugar, eggs, fat--before delving into the techniques that bring recipes to life: texture, color, how things rise, and a technical overview. 100 tested, tried, and true recipes follow and are organized by difficulty and time commitment, ranging from easy 30-minute cakes to spectacular showstoppers you can devote a weekend to, including: Bake in an afternoon: Plum Sandwich Cake, Mocha Chocolate Chip Cake Bars, and 10-minute Mango Cheesecake Bake in a day: Chocolate Mousse Cloud Cake, Fancy Rhubarb Tart with Pistachio Custard, and Olive Oil Brie-oche Bake over a weekend: Clementine Crème Fraiche Ice Cream Cake, Grilled Cheese Za'tar Pain Suisse, and Honey Mandarin Buns Gorgeous photos accompany every recipe and the infographic-style illustrations help home bakers easily grasp the hows and whys of baking, making disasters and flops a thing of the past"--